Spatial Assessment of Soil Fertility Status in Shiratti Sub Watershed of Semi-arid Tropics in Southern India - R, Vasundhara; Hedge, Rajendra; S., Dharumarajan; K. V, Niranjana (International Journal of Bio-resource and Stress Management, 2020)
Spatial variability of soil fertility assessment is necessary for enhancing crop and soil productivity particular of the area. The study was carried out to evaluate the nutrient status of soils in micro watersheds, of Shiratti taluk in Gadag district, Karnataka with objectives of (i) to assess the spatial variability of Soil nutrients at a regional scale through geostatistical methods and to assess the relationships of nutrient availability with several soil properties. Around 831 surface soil samples (0–15 cm depth) were collected from farmer’s fields with total area of 5698 ha, at 250×250 m2 grid interval during 2014–15, using GPS locations. Semivariograms were calculated for all nutrients and their main parameters (nugget effect, sill and range) were obtained. The CV values of measured soil properties ranged from 13.18 for pH and 149 for EC. Among the soil nutrients highest variation was observed in Zinc 126.84 and lowest was in potassium 55.38. Moderate spatial dependence for soil pH, OC, P2O5, K2O, Fe, Mn and Cu and strong spatial dependence for extractable B and EC were observed. Available Fe and Zn deficiencies were noticed in 48 and 83% of the study area, respectively. Majority of the area recorded low in organic carbon, available P2O5, S, and B whereas available K2O is medium to high in status. Soil pH showed significant and negative correlations with the concentrations of extractable available S, B, Fe and Mn and Fe; whereas the available K2O, Zn and Cu correlation was significant and positive with soil organic carbon concentration.